2018
DOI: 10.21083/partnership.v12i2.3957
|View full text |Cite
|
Sign up to set email alerts
|

Community-led Digital Exhibits Service at the Edmonton Public Library: Research and Consultation

Abstract: This paper presents the findings of the community consultation and research conducted as part of the Digital Exhibits Intern Librarian Project at the Edmonton Public Library in 2016. The research project aimed to understand the local context for a new technology service in Edmonton, including the capacity for content creation and partnership among community organizations aligned with the Library's mission. The study consisted of a survey and a series of semi-structured interviews. Findings include identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…(Kelly and O'Gara, 2018) It was concluded that a project should always start with the question of why, and projects to be done should be purposeful. (Zvyagintseva, 2018) Productive methods are required to enhance digital platform growth. (Shelby, 2019) For the PM, the critical quality is to improve productivity.…”
Section: Most Important Results In Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kelly and O'Gara, 2018) It was concluded that a project should always start with the question of why, and projects to be done should be purposeful. (Zvyagintseva, 2018) Productive methods are required to enhance digital platform growth. (Shelby, 2019) For the PM, the critical quality is to improve productivity.…”
Section: Most Important Results In Papersmentioning
confidence: 99%
“…Librarians constantly discover different techniques to use software for functional management (Kipps & Jones, 2020). Productive methods are required to enhance digital platform growth (Zvyagintseva, 2018). Functional communication indicates better outcomes (D'Amato & Erb, 2018).…”
Section: Advantages Of Using Project Managementmentioning
confidence: 99%